Clinical presentation of scrub typhus during a major outbreak in central Nepal - Sedhain, Arun; Bhattarai, Gandhi R. (Asian Journal of Medical Sciences, 2017)
Background: Scrub typhus, an emerging rickettsial disease caused by the organism Orientiatsutsugamushi, is associated with multi-organ involvement. We prospectively studied the clinical manifestations of the disease during a major outbreak in central part of Nepal. Aims and Objective: This study was carried out with an aim to analyze the clinical presentations, laboratory parameters, complications and outcomes of scrub typhus. Materials and Methods: A prospective observational study was conducted in the Department of Medicine in a tertiary teaching hospital. A total of 1398 patients admitted with acute febrile illness were subjected for Scrub Typhus Detect™ IgM ELISA test, among which 502 (35.90%) patients tested positive and were included in the study. Acute kidney injury was defined according to KDIGO guideline. Statistical analysis was done with SAS University Studio package using t-test for continuous variables and chi-square test for categorical variables. Results: Mean age of the patients was 30.37±18.81 years with 26.29% in the pediatric age group (<14 years). Females comprised of 55.98% of the patients. Majority (97.98%) of the patients were seen between July to November. Clinical presentations in the descending order of frequency were anorexia (55.18%), headache (53.39%), lymphadenopathy (15.73%), jaundice (13.35) and eschar (6.57%). Mean scrub typhus IgM ELISA value was 2.17. Leukocytosis was seen in 5.78% and thrombocytopenia in 66.73% of patients. Transaminitis was found in 80.68% of patients. Urinary abnormalities were recorded in 42.3% of patients. Acute kidney injury (AKI) was seen in 35.8% of patients followed by acute respiratory distress syndrome (24.1%), pneumonia (22.1%), shock (14.74%), neurologic manifestation (6.37%) and cardiac manifestations (4.38%). ICU admission was required for 18.73% of patients and 8.57% required ventilator support. Mortality rate was 1.79%. Conclusion: Scrub typhus, being an emerging vector borne infectious disease in Nepalese context, is associated with multiple organ involvement. Asian Journal of Medical Sciences Vol.8(4) 2017 27-31